TEST OF PHOSPHATE FERTILIZER AND DOSAGE OF CHICKEN MANURE ON GROWTH RESPONSE AND YIELD OF EGGPLANT (Solanum melongena L) PLANTS - Rahmaniah Rahmaniah (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
The business of growing eggplant plants is still traditional in Indonesia and does not involve a great deal of intensive cultivation, particularly when it comes to the application of fertilizers to support the growth and yield of eggplant plants. As a result, eggplant plant production is low there. Using the right dose of fertilizer can also help increase production yields. The primary purpose of fertilizer is to provide or add nutrients to the soil that may only be present in trace amounts or not at all. Natural chicken compost and inorganic phosphate manures contain different kinds of supplements and substances required by plants. Consequently, it is important to find the proper portion used to acquire ideal development and yield of eggplant plants. Research Targets To decide the portion of chicken compost and phosphate manure on the development and yield of eggplant (Solanum malongena L). to ascertain how the growth and yield of eggplant (Solanum malongena L) are affected by the dosages of phosphate fertilizer and chicken manure, as well as the optimal interaction between the two substances. In this study, the experimental design was a factorial randomized block design (RBD) with two treatment factors: Factor I: Dosage of chicken manure (A) consisted of 3 levels, namely: = Kontrol,   = 4 kg/plot (6 ton/ha),  = 6 kg/plot (8 ton/ha).  Factor II:  =  Kontrol,  = 4,5 g/plot,  = 9,0 g/plo, = 13,5 g/plot.  Chicken manure dosage varied significantly depending on plant height, primary branch count, sample planting fruit count, sample planting production, and plot production. A2 (6 kg/plot) was the most effective dose of chicken manure in this study. The dosage of phosphate fertilizer was significantly different for plant height, primary branch count, sample planting fruit count, sample crop production, and plot production. P3 (13.5 g/plot) was the NPK fertilizer dose that performed the best in this study. There was no significant difference in plant height, primary branch count, sample planting fruit count, sample crop production, or production per plot between cow manure and phosphate fertilizer doses.